2010
DOI: 10.1021/nl1026869
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Gold Nanorod-Nanoparticle Hybrids into Plasmonic Fano Resonance for Dramatically Enhanced Light Emission and Transmission

Abstract: We investigate the optical response of a gold nanorod array coupled with a semicontinuous nanoparticle film. We find that, as the gold nanoparticle film is adjusted to the percolating regime, the nanorod-film hybrids are tuned into plasmonic Fano resonance, characterized by the coherent coupling of discrete plasmonic modes of the nanorod array with the continuum band of the percolating film. Consequently, optical transmission of the percolating film is substantially enhanced. Even more strikingly, electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 54 publications
3
71
0
Order By: Relevance
“…The local surface plasmon resonance (LSPR) of the AgNRs was tuned to be resonant with the emission peak of the Mn 2+ :(Yb 3+ , Er 3+ )/NaYF 4 crystal. The above parameters provide the best local field enhancement and energy transfer effect, which has been confirmed by our previous work [53,54]. The absorption spectra of the AgNR cavity are presented in Fig.…”
Section: Tuning the Upconversion Pl Of Mn 2+ :(Yb 3+ Er 3+ )/ Nayf supporting
confidence: 85%
“…The local surface plasmon resonance (LSPR) of the AgNRs was tuned to be resonant with the emission peak of the Mn 2+ :(Yb 3+ , Er 3+ )/NaYF 4 crystal. The above parameters provide the best local field enhancement and energy transfer effect, which has been confirmed by our previous work [53,54]. The absorption spectra of the AgNR cavity are presented in Fig.…”
Section: Tuning the Upconversion Pl Of Mn 2+ :(Yb 3+ Er 3+ )/ Nayf supporting
confidence: 85%
“…Fano resonances are characterized by a steeper dispersion than conventional Lorentzian resonances [2,8], which make them promising for local refractive index sensing applications [16], to confine light more efficiently [2] and for surface enhanced Raman scattering (SERS) [19]. Besides these applications, Fano resonances have also been used for enhancing the biosensing performance [20,21], enhanced light transmission [22], slow light [23], and classical analog of electromagnetically induced absorption (EIA) [24]. More recently, Heeg et al [25] reported the use of Fano resonances for interferometric phase detection and x-ray quantum state tomography which provide new avenues for structure determination and precision metrology [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, tremendous attention was attracted to designing various metallic structures to obtain Fano resonance. For example, the plasmonic array structures ranging from particle lattices and oligomers to nanowire lattices and split-ring-type structures [16][17][18][19][20][21][22] were proposed to realize Fano resonance. These reported cases are a little bulky and complicated and have some difficult to integrate.…”
Section: Introductionmentioning
confidence: 99%